Perisai “Kebenaran Informasi” Dalam Delik Penghinaan Presiden Dan Wakil Presiden Menurut Kitab Undang-Undang Hukum Pidana (KUHP) - Ahwan Ahwan; R. Fahmi Natigor Daulay (Universitas Mataram, 2026)
The substance of the offenses of insulting the president and vice president in the Criminal Code has indeed accommodated Constitutional Court Decision No. 013-022/PUU-IV/2006. The change in the nature of the offense to an absolute complaint-based offense and the reduction of the criminal penalty from six years to three years constitute substantial modifications. However, in certain sections, the legislature has retained the old classification, in which the president and vice president are designated as exclusive subjects in the offenses of defamation and insult. This has structural implications that concern not only the issue of freedom of expression but also the burden of proving the “truth of the information,” which serves as a crucial safeguard for citizens in expressing criticism. This article aims to examine how the mechanism for proving “truth of information” is regulated in the Criminal Code. Using doctrinal legal research with a legislative, conceptual, and comparative approach, this article seeks to examine the “truth of information” defense mechanism in defamation offenses involving the President and Vice President as subjects. This article finds that, in both the old and new Criminal Codes, the “truth of information” defense in defamation offenses applies only to “any person” and “public officials”/“civil servants.” This fact demonstrates that criticism of the public and government officials, on the one hand, and criticism of the “president and vice president,” on the other, are afforded different levels of protection. Furthermore, this also has the potential to create a chilling effect and foster a high degree of apathy among citizens regarding the exercise of their freedom of expression.